Somatic symptoms in adolescence as a predictor of severe mental illness in adulthood: a long-term community-based follow-up study - Hannes Bohman; Sara B. Låftman; Neil Cleland; Mathias Lundberg; Aivar Päären; Ulf Jonsson (BMC, 2018)
Abstract Background Somatic symptoms are common and costly for society and correlate with suffering and low functioning. Nevertheless, little is known about the long-term implications of somatic symptoms. The objective of this study was to assess if somatic symptoms in adolescents with depression and in their matched controls predict severe mental illness in adulthood by investigating the use of hospital-based care consequent to different mental disorders. Methods The entire school population of 16-17-year-olds in the city of Uppsala, Sweden, was screened for depression in 1991-1993 (n = 2300). Adolescents with positive screenings (n = 307) and matched non-depressed controls (n = 302) participated in a semi-structured diagnostic interview for mental disorders. In addition, 21 different self-rated somatic symptoms were assessed. The adolescents with depression and the matched non-depressed controls were engaged in follow-up through the National Patient Register 17-19 years after the baseline study (n = 375). The outcome measures covered hospital-based mental health care for different mental disorders according to ICD-10 criteria between the participants' ages of 18 and 35 years. Results Somatic symptoms were associated with an increased risk of later hospital-based mental health care in general in a dose-response relationship when adjusting for sex, adolescent depression, and adolescent anxiety (1 symptom: OR = 1.63, CI 0.55-4.85; 2-4 symptoms: OR = 2.77, 95% CI 1.04-7.39; ≥ 5 symptoms: OR = 5.75, 95% CI 1.98-16.72). With regards to specific diagnoses, somatic symptoms predicted hospital-based care for mood disorders when adjusting for sex, adolescent depression, and adolescent anxiety (p < 0.05). In adolescents with depression, somatic symptoms predicted later hospital-based mental health care in a dose-response relationship (p < 0.01). In adolescents without depression, reporting at least one somatic symptom predicted later hospital-based mental health care (p < 0.05). Conclusions Somatic symptoms in adolescence predicted severe adult mental illness as measured by hospital-based care also when controlled for important confounders. The results suggest that adolescents with somatic symptoms need early treatment and extended follow-up to treat these specific symptoms, regardless of co-occurring depression and anxiety.